REPRESENTASI UNGKAPAN-UNGKAPAN BAHASA LAMAHOLOT LINGKUNGAN KELAUTAN MASYARAKAT DESA BAHINGA TERHADAP PENINGKATAN NILAI-NILAI PENDIDIKAN KARAKTER - Fransiska Jone Mare; Fransiska Jone Mare (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2021)
The article explains about the representation of maritime-metaphors of Lamaholot Language of Bahinga Community in Increasing the values of educational character. The aims of this article are to find the kinds of maritime-metaphor and to find the representation of those metaphors in building the students’ characters. Research approaches in this article is descriptive qualitative. The data retrieved by using observation and interview as main data and secondary data is taken from the thesis. The results show that there are nine maritime-metaphors of Lamaholot Language of Bahinga Community can be used in increasing the values of educational character.